NASAL cytology: practical aspects and clinical relevance. Issue 6 (June 2016) - Gelardi, M.; Iannuzzi, L.; Quaranta, N.; Landi, M.; Passalacqua, G.
Summary: Nasal cytology is a simple and safe diagnostic procedure that allows to assess the normal and pathological aspects of the nasal mucosa, by identifying and counting the cell types and their morphology. It can be easily performed by a nasal scraping followed by May–Grunwald–Giemsa staining and optical microscopy reading. This procedure allows to identify the normal cells (ciliated and mucinous), the inflammatory cells (lymphocytes, neutrophils, eosinophils, mast cells), bacteria, or fungal hyphae/spores. Apart from the normal cell population, some specific cytological patterns can be of help in discriminating among various diseases. Viral infections, allergic rhinitis, vasomotor rhinitis and overlapping forms can be easily identified. According to the predominant cell type, various entities can be defined (named as NARES, NARESMA, NARMA). This implies a more detailed knowledge and assessment of the disease that can integrate the standard diagnostic procedures. Nasal cytology also represents a useful research tool for diagnosis and therapy.